Behavioral intention to use forensic accounting services for the detection and prevention of fraud by large Malaysian companies - Muthusamy, Gunasegaran (Curtin University, 2011)
This study investigates the factors that influence the behavioral intention to use forensic accounting services in the detection and prevention of fraud by large Malaysian companies. The research was motivated by the underutilization of forensic accounting services, an essential and effective fraud detection and prevention method. The low usage of this service by companies in Malaysia and worldwide has been pointed out as a contributing factor in the escalation of fraud. The organizational intention to use professional services including forensic accounting services have not been researched previously.The research adopts a multi-phased mixed method research approach. In the first phase, the literature review identified the Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB), Health Belief Model (HBM) and Hierarchy of Effects Model (HOE) as relevant to the study of behavioral intention. The four theories were then cross-examined to conceptualize key constructs relevant to this study to form the initial model. The second phase consist of qualitative data collection from ten large Malaysian companies’ Chief Financial Officers (CFO). The semi-structured interview data is analyzed via a two stage content analysis technique and the initial research model is amended based on the findings. Altogether, eighteen constructs were identified and categorized into seven factors. In the ensuing quantitative phase, a survey instrument, developed to test the model, is utilized in a pilot study on 30 CFOs from large Malaysian companies. The instrument is then refined and administered in a national survey which resulted in 305 useable responses.Quantitative data is analyzed using Partial Least Square based Structural Equation Modeling. The results confirm the significant positive influence of attitude, organizational ethical climate, stakeholder pressure, perceived severity of fraud, and the negative influence of financial costs on the behavioral intention to use forensic accounting services. In addition, the moderating effect of organizational size and organizational type on the relationship between behavioral intention and its direct antecedents is supported.This study has both theoretical and practical contributions. The theoretical contribution lies in the integrative conceptual model that has successfully incorporated constructs from the TRA, TPB, HBM, and HOE in investigating the behavioral intention to use forensic accounting services. The organizational intention to use professional services including forensic accounting services have not been investigated previously. This study is also the first ethical decision-making model to incorporate threat perceptions from HBM and awareness from HOE. Finally, perceived risks and perceived benefits from HBM, previously thought to be equivalent to attitude from TPB, have instead been established as significant direct antecedents of attitude.Practically, the findings of this study enables the Malaysian government, professional bodies, company board of directors, organizational stakeholders, and accounting firms to improve their understanding on why organizations resist the use of forensic accounting services in the detection and prevention of fraud. It will also allow them to devise practical methods and promotion strategies to increase the awareness, acceptance, and ultimately the use of forensic accounting services in the fight against fraud.